Prolonged Esophagitis After Primary Dysfunction of the Pyloric Sphincter in the Rat and Therapeutic Potential of the Gastric Pentadecapeptide BPC 157 - Ivan Dobric; Petar Drvis; Igor Petrovic; Drazen Shejbal; Luka Brcic; Alenka Boban Blagaic; Lovorka Batelja; Marko Sever; Neven Kokic; Ante Tonkic; Ivan Zoricic; Sandro Mise; et al. (Elsevier, 2007)
Seven or fourteen days or twelve months after suturing one tube into the pyloric sphincter (removed by peristalsis by the seventh day), rats exhibit prolonged esophagitis with a constantly lowered pressure not only in the pyloric, but also in the lower esophageal sphincter and a failure of both sphincters. Throughout the esophagitis experiment, gastric pentadecapeptide BPC 157 (PL 14736) is given intraperitoneally once a day (10 µg/kg, 10 ng/kg, last application 24 h before assessment), or continuously in drinking water at 0.16 µg/ml, 0.16 ng/ml (12 ml/rat per day), or directly into the stomach 5 min before pressure assessment (a water manometer connected to the drainage port of a Foley catheter implanted into the stomach either through an esophageal or duodenal incision). This treatment alleviates i) the esophagitis (macroscopically and microscopically, at either region or interval), ii) the pressure in the pyloric sphincter, and iii) the pressure in the lower esophageal sphincter (cmH2O). In the normal rats it increases lower esophageal sphincter pressure, but decreases the pyloric sphincter pressure. Ranitidine, given using the same protocol (50 mg/kg, intraperitoneally, once daily; 0.83 mg/ml in drinking water; 50 mg/kg directly into the stomach) does not have an effect in either rats with esophagitis or in normal rats. Keywords:: stable gastric pentadecapeptide BPC 157, ranitidine, pyloric sphincter dysfunction, sphincter pressure, rat esophagitis